RECK-Mediated Inhibition of Glioma Migration and Invasion - Silveira Correa, Tatiana C.; Massaro, Renato Ramos; Brohem, Carla Abdo; Taboga, Sebastiao Roberto [UNESP]; Lamers, Marcelo Lazzaron; Santos, Marinilce Fagundes; Maria-Engler, Silvya Stuchi (Wiley-liss, 2010)
RECK is an anti-tumoral gene whose activity has been associated with its inhibitory effects regulating MMP-2, MMP-9, and MT1-MMP. RECK level decreases as gliobastoma progresses, varying from less invasive grade II gliomas to very invasive human glioblastoma multiforme (GBM). Since RECK expression and glioma invasiveness show an inverse correlation, the aim of the present study is to investigate whether RECK expression would inhibit glioma invasive behavior. We conducted this study to explore forced RECK expression in the highly invasive T98G human GBM cell line. Expression levels as well as protein levels of RECK, MMP-2, MMP-9, and MT1-MMP were assessed by qPCR and immunoblotting in T98G/RECK+ cells. The invasion and migration capacity of RECK+ cells was inhibited in transwell and wound assays. Dramatic cytoskeleton modifications were observed in the T98G/RECK+ cells, when compared to control cells, such as the abundance of stress fibers (contractile actin-myosin II bundles) and alteration of lamellipodia. T98G/RECK+ cells also displayed phosphorylatecl focal adhesion kinase (P-FAK) in mature focal adhesions associated with stress fibers; whereas P-FAK in control cells was mostly associated with immature focal complexes. Interestingly, the RECK protein was predominantly localized at the leading edge of migrating cells, associated with membrane ruffles. Unexpectedly, introduced expression of RECK effectively inhibited the invasive process through rearrangement of actin filaments, promoting a decrease in migratory ability. This work has associated RECK tumor-suppressing activity with the inhibition of motility and invasion in this GBM model, which are two glioma characteristics responsible for the inefficiency of current available treatments. J. Cell. Biochem. 110: 52-61, 2010. (C) 2010 Wiley-Liss. Inc.
Keywords: GLIOBLASTOMA; RECK GENE; CYTOSKELETON; INVASION; Migration; MMP